Novel Arthrogryposis Multiplex Congenita Presentation in a Newborn With Pierpont Syndrome - Joana Pereira-Nunes MD; Ana Vilan MD; Ana Grangeia MD; Renata d'Oliveira MD (SAGE Publishing, 2023)
Pierpont syndrome is a rare and recently described multiple congenital anomaly syndrome, classically characterized by global developmental delay, distinctive facial dysmorphic features, and abnormal fat distribution in distal limbs. Only few cases were previously documented. We report a case of a term male neonate admitted to the neonatal intensive care unit because of feeding difficulties. Intrauterine growth restriction, microcephaly, and bilateral equinovarus foot were diagnosed in the second trimester, and prenatal array comparative genomic hybridization showed no abnormality. Physical examination revealed bilateral flexion deformities of wrists, elbows, knees and clubfoot, large hands and feet, deep palmar and plantar grooves, and calcaneo-plantar fat pads. Craniofacial dysmorphism, axial hypotonia, and hypoactivity were also observed. Due to the presence of congenital and non-progressive joint contractures, arthrogryposis multiplex congenita (AMC) was considered. A comprehensive diagnostic workup, including a Next Generation Sequencing target panel, was performed but did not establish a diagnosis. The clinical exome identified an heterozygous pathogenic variant in the TBL1XR1 gene (NM_001321194.1: c.1337A>G, p.[Tyr446Cys]), allowing Pierpont syndrome diagnosis. Our case stands out for reporting the novel AMC presentation in a Pierpont syndrome newborn. The broader and precocious genetic testing proved to be an essential clarifying diagnostic tool. Our patient supports the relation between the p.Tyr446Cys sequence variant in TBL1XR1 gene with this rare syndrome, reinforcing its association with a distinctive and recognizable phenotype, as well as expanding its clinical features to include AMC.